The Influence of Accent Distance on Perceptual Adaptation in Toddlers and Adults. Issue 1 (2nd January 2023) - Cooper, Angela; Paquette-Smith, Melissa; Bordignon, Caterina; Johnson, Elizabeth K.
ABSTRACT: Foreign accents can vary considerably in the degree to which they deviate from the listener's native accent, but little is known about how the relationship between a speaker's accent and a listener's native language phonology mediates adaptation. Using an artificial accent methodology, we addressed this issue by constructing a set of three artificial accents (Near, Far, and Farther), varying in the number and magnitude of pronunciation deviations from standard Canadian English. These accents were presented to toddlers and adults in an eye-tracking task. Regardless of accent type, adults readily adapted to the exposed pronunciation change. Adults exposed to the Farther accent were also more willing to accept novel pronunciation changes. Young toddlers exposed to Far or Farther accents showed no evidence of acquiring the exposed pronunciation change and demonstrated worse word recognition for standard Canadian-accented words. These findings suggest that when a speaker's accent deviates substantially from a young toddler's native accent, this may lead to a significant decrement in their ability to recognize not only an unfamiliar accent but also native-accented speech. Overall, these findings provide a well-controlled test of competing models of accent adaptation and generate multiple hypotheses to be examined in the future using more ecologically valid stimuli.